Analyzing the relationship between economic growth and electricity consumption from renewable and non-renewable sources: Fresh evidence from newly industrialized countries. (April 2021) - Azam, Anam; Rafiq, Muhammad; Shafique, Muhammad; Zhang, Haonan; Ateeq, Muhammad; Yuan, Jiahai
Abstract: This study analyzes the impact of renewable electricity consumption on economic growth for the panel of 10 newly industrialized countries from 1990 to 2015. For this, panel unit root tests, panel heterogeneous co-integration method, panel Fully Modified Ordinary Least Square and the Granger causality method are employed. The primary outcomes of this study are as follows: (1) panel unit root test and panel co-integration method confirm that the economic growth, renewable electricity consumption, non-renewable electricity consumption, gross capital formation, labor force and trade openness are co-integrated, (2) panel Fully Modified Ordinary Least Square confirms that all studied variables have a positive long-run effect on economic growth, a 1% increase in renewable and non-renewable electricity consumption increased economic growth by 0.095% and 0.017% respectively, (3) the outcomes from Granger causality test also illustrates that there is bidirectional causation between renewable electricity consumption and economic growth in both the short-run and long-run that supports the feedback hypothesis. From the empirical findings, the feedback hypothesis is valid for newly industrialized countries.